10% Human: How Your Body's Microbes Hold the Key to Health and Happiness - Alanna Collen (William Collins, 2015)
"This groundbreaking guide reveals how our personal colony of microbes run 90 per cent of our bodies, challenging how we view diet, modern disease and medicine. Microbes influence our gut, weight, immune system, mental health and even our choice of partner, and so understanding them can unlock many of the mysteries of modern diseases - including obesity, autism, mental health problems, gut disorders, allergies, autoimmunity and even cancer. As biologist and zoologist Dr Alanna Collen argues, these conditions are rooted in our lack of care for our microbes, and this is the indispensable study: life - and becoming a healthy human - is impossible without them."--Back cover.